Electrodialytic treatment of secondary mining resources for raw materials extraction - Almeida, Joana (2022)
This work received funding from the European Unions Horizon 2020 research and innovation program under the Marie Skłodowska-Curie grant agreement No. 778045 , and from Portuguese funds from FCT / MCTES through grant UIDB/04085/2020 . J. Almeida acknowledges Fundação para a Ciência e a Tecnologia and EcoCoRe Doctoral program for her PhD fellowship PD/BD/135170/2017 .